Evalution of Using Virtual Laboratory Media to Learning Geometry in Mathematic Programe Open University - Nurmawati, Nurmawati; Ismartoyo, Ismartoyo (International Journal of Research in Education, 2024)
The current condition of the virtual laboratory is developing so rapidly, one indicator is the number of Mathematics students in open university who are looking for references related to practical geometry courses via online between lectures, this raises concern as a lecturer in adding value to lectures, which are adapted to the 21st century learning era today by creating virtual laboratories based on Virtual Reality, research methods using the ADDIE R D model (Analysis, Design, Develop, Implementation and Evaluation), the science virtual lab product has not been developed much in Indonesia, another thing that makes the appeal of this virtual lab product is that it is able to display virtual reality which can increase motivation and learning outcomes. Student, based on the validation of media experts and material experts on the virtual geometry lab product, it scores 91 and 94 meaning that the virtual geometry lab product is very suitable for use, then more than 90% of lecturers and students at the Open University are very happy to use it. This research has shown that using virtual geometry labs in geometry learning at the Open University shows that all students show enthusiasm in using virtual geometry lab products as a supplement to geometry learning inside and outside the classroom. This was shown that after limited testing of virtual geometry lab products in the open university mathematics education study program, it showed that the majority had completedÂ  B+ or a score above 85 in geometry learning.